2021
DOI: 10.1002/aqc.3593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spatial distribution models to predict subtidal burying habitat of the forage fish Ammodytes personatus in the Strait of Georgia, British Columbia, Canada

Abstract: The Pacific sand lance (Ammodytes personatus) is a key forage species for many commercially important fish (e.g. salmon and groundfish), marine birds, and whales found in nearshore coastal waters of British Columbia, Canada. Sand lance lack a swim bladder and have a requirement for low‐silt, medium‐coarse sandy sea‐bed habitat for burying. Little information is available describing the distribution of burying habitat, partly because there are no commercial fisheries for A. personatus in British Columbia. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…AUC (a threshold-independent measure) and TSS statistics were used for estimate accuracy in the models performance. The AUC curve obtained from the Receiving Operator Characteristic (ROC) curve which is an effective indicator of threshold and prevalence for model performance evaluation [5,14,36,40]. In a model that lacks the ability to detect and predict, the AUC is 0.5 and a very high predictive and detectable model will have an AUC equal or close to 1 [5,41] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AUC (a threshold-independent measure) and TSS statistics were used for estimate accuracy in the models performance. The AUC curve obtained from the Receiving Operator Characteristic (ROC) curve which is an effective indicator of threshold and prevalence for model performance evaluation [5,14,36,40]. In a model that lacks the ability to detect and predict, the AUC is 0.5 and a very high predictive and detectable model will have an AUC equal or close to 1 [5,41] .…”
Section: Discussionmentioning
confidence: 99%
“…It is noticeable that plants can shift their geographic ranges as a response to climatic change [56] . So new patterns of plant occupancy/ abundance can affect on animals which rely on plant availability for both food and shelter [31,36,[57][58][59] . However it cannot be ignored that it is possible for brown bears to cope with this food challenge due to climate change as they have a wide food niche [60] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that intertidal spawning habitat is located near subtidal burying habitat (Haynes and Robinson 2011;Laugier et al 2015). A layer representing the proximity to predicted suitable subtidal habitat (from Robinson et al 2021)) was created by calculating the distance of each raster cell from the closest neighboring cell where predicted subtidal habitat suitability from Robinson et al (2021) was 0.54 or greater.…”
Section: Rationale For Environmental Predictor Selectionmentioning
confidence: 99%
“…Spatially explicit predictions of suitable habitat for sand lance could identify habitat for protection as well as aid managers in assessing the cumulative impacts of multiple pressures including shoreline armouring, dock installation, ship anchoring, and marina development. Recent modelling work has shown that suitable subtidal benthic habitats for sand lance in the Salish Sea are limited and patchy (Robinson et al 2021;Greene et al 2021;4 1995Tomlin et al 2021). No environmental cues that trigger spawning, such as sea surface temperature, tidal and lunar cycles have yet been identified.…”
Section: Introductionmentioning
confidence: 99%